A ciência do século XIX na visão do jornalista João Ribeiro em artigos de divulgação científica (1895-1934) - Oliveira, Filipe Silva de (2017)
This dissertation seeks to identify visions of science expressed in articles published by the journalist João Ribeiro at the turn of the 19th century for the 20th century, as well as to verify and analyse the context in which the journalist was inserted in the social, scientific, political and philosophical sphere. The methodological approach used in the analysis of the information present in articles of scientific dissemination was the Content Analysis contained in works by Bardin (1977, 2009, 2011), accompanied by the theory of Cachapuz (2005). The results point to 7 (seven) categories of science vision: 1. Permeated of contradictions, 2. Refutable, 3. Citizen; 4. Ironic; 5. Masculine; 6. Investigative; And 7. Criticism. Based on the two mentioned theorists we arrive at the definition of 4 (four) thematic types listed: Scientific Personality, Medicine, Scientific Discovery; And Education Sciences. The conclusions attest that João Ribeiro divulged science in the field of scientific journalism, acting in an advanced way for his time and reporting facts and discoveries during a period of many scientific achievements. The views of science of João Ribeiro serve as a parameter for the understanding of how the first initiatives of scientific dissemination were made in Brazil and of how was the dissemination of scientific knowledge among the common public.